2002
DOI: 10.1002/1521-3803(20020101)46:1<2::aid-food2>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal ions on structure and activity of papain from Carica papaya

Abstract: Papain, a powerful proteolytic enzyme, is an endoprotease belonging to cysteine endopeptidase family. It is used extensively in food processing especially in tenderization of meat. In this study, we have made an attempt to show the structure activity relationship of this enzyme and the role of calcium and magnesium ions in the activity and stability of the enzyme. Results of activation and stabilization of the enzyme by these cations showed concentration dependent effect. The enzymatic activity of papain incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
1
17
1
2
Order By: Relevance
“…The effects of different concentrations of Ca 2+ on fruit bromelain activity implied that the trend of the response to increasing ion concentration was consistent. These results corroborate the earlier observations ( (Kaul et al 2002;Wang et al 2009), which implied that calcium ions promote the bromelain activity by stabilizing the secondary structure of enzyme. The hydrolysis of gelatin was enhanced by 37.52 % at 0.3 mM-0.5 mM Ca 2+ ions (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The effects of different concentrations of Ca 2+ on fruit bromelain activity implied that the trend of the response to increasing ion concentration was consistent. These results corroborate the earlier observations ( (Kaul et al 2002;Wang et al 2009), which implied that calcium ions promote the bromelain activity by stabilizing the secondary structure of enzyme. The hydrolysis of gelatin was enhanced by 37.52 % at 0.3 mM-0.5 mM Ca 2+ ions (Fig.…”
Section: Resultssupporting
confidence: 93%
“…It is a single polypeptide chain containing 212 residues, having seven cysteine residues, which may selectively interact with mercury ions (Kaul et al, 2002). Therefore, we supposed that if we functionalized AuNPs with papain, we could detect Hg 2+ using P-AuNPs just by our naked eyes.…”
Section: Characterization Of P-aunpsmentioning
confidence: 99%
“…These studies revealed that the proteolytic activity of caspase 6 can indeed be inhibited by direct binding of zinc to an exosite distal to the active site (48), whereas caspase 9, which harbors two zinc binding sites, namely, an active site and an exosite, was shown to be inhibited to a greater extent following the biding of zinc to the active site that harbors the catalytic dyad 287 Cys and 237 His (44). Similar studies done on papain, a cysteine protease derived from the papaya plant, reported that calcium and/or magnesium enhances the proteolytic activity of papain (45), whereas zinc and/or cadmium was shown to inhibit its activity (47). We can conclude that metal (especially zinc)-mediated inhibition of proteolytic activity of cysteine proteases has been a topic of thorough investigation; however, to our knowledge, metal-mediated inhibition of pathogenic bacterial proteases, and GAS in particular, is a novel mode of inhibition that we report here for the first time.…”
Section: Discussionmentioning
confidence: 72%
“…Nonetheless, several other laboratories reported the regulation of other cysteine proteases by metal ions, including zinc (44)(45)(46)(47)(48). For example, human apoptotic caspases, a family of cysteine proteases involved in apoptosis, are a recognized model for studying zinc-mediated inhibition of proteolytic activity (44,46,48).…”
Section: Discussionmentioning
confidence: 99%